2020
DOI: 10.1038/s41370-020-00270-9
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of urinary concentrations of phthalate and phthalate alternative metabolites among reproductive-aged Black women from Detroit, Michigan

Abstract: Background: Phthalates are endocrine-disrupting chemicals that are widely present in consumer products. In the United States, Black women are more highly exposed to phthalates than other racial/ethnic groups, yet information on predictors of phthalate exposure among Black women is limited. Objective: We evaluated the association of demographics, lifestyle, reproductive history, and personal care product use with urinary concentrations of phthalate and phthalate alternat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 58 publications
1
15
0
Order By: Relevance
“…These race and ethnicity trends are consistent with the results of previous studies. 6,7,11 Though we did not collect data on specific brands or product constituents, prior work has shown that the products marketed to Black/African American women tend to have higher levels of potentially harmful chemicals, 5,6,14,29 further augmenting the exposure burden for this demographic group. 7 Women were fairly consistent in their reported use of both products, and reliability improved further when more general classifications of ever versus never use were compared.…”
Section: Discussionmentioning
confidence: 99%
“…These race and ethnicity trends are consistent with the results of previous studies. 6,7,11 Though we did not collect data on specific brands or product constituents, prior work has shown that the products marketed to Black/African American women tend to have higher levels of potentially harmful chemicals, 5,6,14,29 further augmenting the exposure burden for this demographic group. 7 Women were fairly consistent in their reported use of both products, and reliability improved further when more general classifications of ever versus never use were compared.…”
Section: Discussionmentioning
confidence: 99%
“…We considered personal care products as potential correlates of biomarker EDC concentrations based on our prior analyses in the SELF cohort. Product use correlates were assessed at baseline using questionnaires and included reported use (yes or no) of vaginal deodorant, vaginal powder, and cosmetics (makeup, lotion before bed, perfume, and nail polish) in the past 24 h. We also assessed the frequency of sunscreen use while outside, which was reported as never/hardly ever, sometimes, often, or always/nearly always. We dichotomized sunscreen use (never/hardly ever vs any reported use) given small sample sizes in several strata.…”
Section: Methodsmentioning
confidence: 99%
“…Details of sample collection and quality control have been described previously. 23,24 Briefly, we collected spot urine samples from participants during the baseline visit at Henry Ford Health, which were stored at −80 °C until shipped on dry ice overnight to the NIEHS biorepository, where they were stored at −80 °C. Urine samples were then shipped overnight from the NIEHS to the CDC on dry ice for quantification of EDCs using online solid phase extraction coupled with highperformance liquid chromatography isotope dilution tandem mass spectrometry, as described previously.…”
Section: Study Populationmentioning
confidence: 99%
“…Because both PCA and k- means clustering are sensitive to outlier values, , we performed a sensitivity analysis that identified and removed outliers using Rosner’s generalized extreme Studentized deviate test to determine if outlier biomarker concentrations affected overall correlate associations. Finally, we re-ran our regression models with a reduced number of correlates, as done previously in SELF, to ensure that our main findings were not biased by conditioning on mediators or colliders. We selected correlates for these models based on previously identified correlates of exposure in the SELF cohort. …”
Section: Methodsmentioning
confidence: 99%